Manajemen Strategik dan Mutu Pendidikan Islam - Ahmad Khori (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
A qualified education is an education which is able to develop nation character as well as civilization. Therefore, the values of faith, obedience, piousness, virtuous acts, healthiness, knowledge, competence, creativity, self-reliance, democracy and responsibility should be strengthened within educational institutions including students and stakeholders. Nowadays, most schools superficially develop some of the educational aspects, such as, cognitive dimension that is taught through memorizing and psychomotor dimension which is merely a mechanistic process. Meanwhile, other dimensions, such as relational dimension, are not handled properly. Ideally, a qualified school should be able to develop cognitive dimension, not only as a memorization but also as knowledge mastery suitable to students’ capacity as well as their endowment. From this phenomenon, I tried to offer a concept of implementation and development of Islamic education within strategic management framework related to teaching-learning process both in formal and non- formal schools. The aim is to fortify students so that they will keep holding onto Qur’an, Hadits, Ijma’ and Qiyas in this global era. Core concept of the strategic management in Islamic education is indeed still novel. Therefore, it is expected that this article can be used in broader area of Islamic education. Moreover, it is also hoped that it will positively affect resources allotment effectiveness in order to achieve the objective of national education. One way is through SWOT analysis, so that institutions of the Islamic education will be able to produce well-qualified graduates who play significant roles in society.